Ambulatory 24 hour intraoesophageal pH and pressure recordings v provocation tests in the diagnosis of chest pain of oesophageal origin. Issue 7 (July 1990) - Ghillebert, G; Janssens, J; Vantrappen, G; Nevens, F; Piessens, J
Abstract : Fifty patients with non-cardiac chest pain underwent 24 hour intraoesophageal pH and pressure recording and provocation tests to determine the relative value of both techniques in establishing the oesophageal origin of the chest pain. Twenty six patients (52%) had at least one positive provocation test: the acid perfusion test was positive related in 18 patients (36%), the edrophonium test in 16 patients (32%), the vasopressin test in five patients (10%), and the balloon distension test (performed in only 20 patients) in one (5%). The 24 hour pH and pressure recording correlated spontaneous chest pain attacks with abnormal motility or gastro-oesophageal reflux in 19 patients (38%). Fourteen of these patients also had at least one positive provocation test. Therefore, 24 hour pH and pressure recordings are only slightly better than a set of provocation tests in identifying the oesophagus as the cause of chest pain (10% diagnostic gain). In the case of oesophageal chest pain, however, 24 hour recording appeared to be the only way to identify the nature of the underlying oesophageal abnormality that caused the spontaneous pain attacks--for example, gastro-oesophageal reflux, motility disorders, or irritability of the oesophagus.